Analysis of the physical and photoelectrochemical properties of c-Si(p)/a-SiC:H(p) photocathodes for solar water splitting - Mejia, Maria del Carmen (2021)
This research was funded by FONDECYT (National Fund for Scientific, Technological Development and Technological Innovation) under the agreement 147-2017. The author M Mejia has been supported by the CONCYTEC Peru (National Council for Science, Technology and Technological Innovation) doctoral scholarship under the Contract Number 236-2015-FONDECYT as well as by the PUCP vicechancellorship for research (VRI, Project No. CAP-2019-3-0041/702). The authors would like to thank the Katholischer Akademischer Auslander-Dienst institution (KAAD) for the short-term grants given to conduct research internships in the Technische Universitat Ilmenau (TU Ilmenau). Finally, the authors would like to thank the German Research Foundation (DFG) (DFG-Gz: INST 273/56-1 FUGG) and the Materials Characterization Center (CAM) at PUCP, for the financial support to conduct the characterization experiments.